Experiences and Perceived Self-Efficacy in Distance Learning Among Teachers of Students With Special Educational Needs - Maurer, Jenny; Becker, Angelika; Hilkenmeier, Johanna; Daseking, Monika (Frontiers in Psychology, 2021)
COVID-19 has great impact for school learning, this is especially true for children with special needs. The major challenges students face during distance learning can be influenced by the teachers’ perceived self-efficacy in distance learning. The present study aimed to investigate the experiences in distance learning of teachers teaching students with special educational needs at special schools and at inclusive schools during COVID-19 in Germany. N = 96 teachers from special schools and inclusive schools were surveyed via an online questionnaire. In general, no differences in allover experiences and perception between teachers of special schools and teachers of inclusive schools could be found. Regardless of the type of school the teachers’ perceived self-efficacy in distance learning is rather low. Furthermore, the result that the support of students with difficulties in mathematics is significant more challenging than the identification of it appeals particularly noteworthy. Due to the assumed heterogeneity between the different special needs of the students, a differentiated consideration should be made with regard to their special educational needs.